Thrombinuria as a link between intrarenal coagulation and inflammation in patients with glomerulonephritis - I. Mykhaloiko; R. Yatsyshyn; I. Dudar (Ukrainian Journal of Nephrology and Dialysis, 2025)
To investigate urinary thrombin levels in patients with glomerulonephritis (GN), evaluate their relationship with the morphological type of GN, disease activity, and assess the diagnostic value of thrombinuria.Methods. A cross-sectional study was conducted in 72 patients with biopsy-proven GN and 40 healthy controls. Serum and urinary concentrations of thrombin, IL-6, TNF-α, and TGF-β1 were measured using ELISA. Clinical data and renal biopsy findings were analyzed. Statistical methods included correlation and group comparison tests.Results. Urinary thrombin was markedly elevated in GN patients compared with controls (median 9.4 vs. 0.38 ng/ml; p = 0.013), while serum thrombin showed no significant difference. Thrombinuria was detected in 80.6% of patients and correlated positively with daily proteinuria (r = 0.514), urinary IL-6 (r = 0.438), and urinary TNF-α (r = 0.372). An inverse correlation was observed with urinary TGF-β1 (r = –0.534) and the chronicity index (r = –0.783), suggesting that thrombinuria characterizes active inflammatory phases, while its decline accompanies fibrotic remodeling. No significant associations were found between serum thrombin and systemic inflammatory markers.Conclusions. Thrombinuria may reflect local activation of coagulation–inflammation pathways. It demonstrates associations with proteinuria, pro-inflammatory cytokines. These results suggest that thrombinuria could serve as a potential non-invasive biomarker of disease activity in GN; however, due to the cross-sectional design and limited sample size, the findings should be interpreted with caution and confirmed in larger longitudinal studies.